The scenario of culture and school practices in the normal school (1946-1971): Contributions to teacher education (Research, Society and Development, 2021)
This article presents the excerpt of a research developed in an Academic Masters in Teaching course at a university in the interior of Rio Grande do Sul, Brazil. It aimed to investigate which school practices permeated the Escola Normal and the culture of this educational institution, in the Brazilian socio-historical scenario, from 1946 to 1971. The time frame marks the existential trajectory of the Brazilian legislation for this training. Methodologically, this is a qualitative and bibliographic research, with empirical data obtained from the CAPES Theses and Dissertations Catalog, analyzed based on Content Analysis. Thirteen studies were found (ten dissertations and three theses), which emerged in the following categories: (a) origin of the normal school, (b) its expansion, (c) and decline. Results indicated that in the period of formation of the normalists, the traditional school reigned, their practices were built in a repressive universe, impregnated with dogmas, between contradictions and political, ideological, gender and class dilemmas, reflected in the professional performances of the normalists. Finally, it is hoped that research like this can clarify the historical aspects and training practices, exposing the intentions that established, distinguished and, from what we have seen, devalued these institutions.